2011
DOI: 10.1007/s10555-011-9335-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential molecular targets for inhibiting bone invasion by oral squamous cell carcinoma: a review of mechanisms

Abstract: Bone invasion is a common characteristic of oral squamous cell carcinoma (OSCC), with adverse affects on patient functionality and survival. Recent studies suggest that it is osteoclasts, rather than malignant keratinocytes themselves, which play the major role in facilitating the entry of the tumour into bone, and its progression within bone. Osteoclasts respond to a variety of local signalling pathways, initiated by products of the malignant epithelial cells. In the present review, we firstly introduce the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 88 publications
1
73
0
4
Order By: Relevance
“…33 Th17 cells have been shown to increase the amount of neutrophils as well as eosinophils to areas of inflammation and even account for the inflammatory lesions in ulcerative colitis. 38,39 This increase in Th17 cells we found may be 1 of the factors driving polyp formation, and further studies need to be undertaken to characterize the intracellular cytokine profiles of these Th17 cells to get a better understanding of their function in CRS.…”
Section: Discussionmentioning
confidence: 78%
“…33 Th17 cells have been shown to increase the amount of neutrophils as well as eosinophils to areas of inflammation and even account for the inflammatory lesions in ulcerative colitis. 38,39 This increase in Th17 cells we found may be 1 of the factors driving polyp formation, and further studies need to be undertaken to characterize the intracellular cytokine profiles of these Th17 cells to get a better understanding of their function in CRS.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study has suggested that it is osteoclasts, rather than malignant keratinocytes, that are more important in facilitating entry of the tumor into bone and its progression thereafter. 17 Ogura et al 15 concluded that maxillary bone invasion was an indicator of cervical metastasis, because patients with bone invasion had a lower 5-year OS rate. Ebrahimi et al 18 reported that bone invasion was an important predictive factor of oral cancer, and that the extent of bone invasion affects clinical T stage and the surgical procedure used.…”
Section: Discussionmentioning
confidence: 99%
“…1 The 5-year survival rate of advanced patients has been improved only marginally over the past decades despite recent advances in surgery and target therapy. 2 HNSCC has recently been recognized as an immunosuppressive disease, 3 suggesting the potential use of immunotherapy to improve patient survival.…”
Section: Introductionmentioning
confidence: 99%